The Influence of Rationalism on the Tafsir al-Manar - Mambauddin, Moch Anwar (Jurnal Semiotika Quran, 2025)
The rise of Rationalism as a philosophical school has exerted influence not only on the disciplines of education, law, and politics, but has also permeated broader aspects of human life, including the domain of religion. One of the central implications of Rationalism is its insistence on placing human reason as a primary instrument for attaining truth and knowledge. This study seeks to examine Tafsir al-Manâr, a seminal work of Muhammad Abduh dan Rasyîd Ridhâ, who endeavored  to  interpret  religion  through a  rationalist framework. Employing a library-based research design with a descriptive–analytical approach, this study utilizes Tafsir al-Manâr as the primary source, complemented by scholarly articles and books that discuss the intellectual contributions of Muhammad Abduh dan Rasyîd Ridhâ. The findings indicate that: (1) both scholars privilege the role of reason in understanding the Qur’an, considering it an indispensable means for the attainment of truth; (2) they repudiate the practice of taqlîd, asserting that religious commitment must rest upon sound proofs and demonstrative evidence; (3) Qur’anic  verses  pertaining to   natural   phenomena  (âyât kauniyyah) ought  to be interpreted through scientific inquiry rather than mystical or mythological explanations;  (4) legal rulings must remain responsive to changing socio-historical contexts and must align with the objectives of Islamic law (maqâshid syarî’ah), and 5) The Tafsir al-Manâr marks a new direction in the reformulation of Qur’anic exegesis methodology, shifting from a predominantly textual approach to one that is contextual and rational, and from mere textual understanding toward actively addressing contemporary social issues.